2019
DOI: 10.1096/fj.201802172r
|View full text |Cite
|
Sign up to set email alerts
|

Diallyl disulfide alleviates inflammatory osteolysis by suppressing osteoclastogenesis via NF‐κB–NFATc1 signal pathway

Abstract: Skeletal homeostasis is closely effectuated by the regulation of bone formation and bone resorption. Osteoclasts are multinuclear giant cells responsible for bone resorption. Overactivated osteoclasts and excessive bone resorption result in various lytic bone diseases, such as osteoporosis, osteoarthritis, periprosthetic infection, and inflammatory aseptic loosening of orthopedic implants. In consideration of the severe side effects caused by the currently available drugs, exploitation of novel drugs has gradu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 68 publications
2
38
0
Order By: Relevance
“…Studies have demonstrated that LPS can promote osteoclast differentiation by enhancing COX-2 expression and activating RANK, JNK and ERK1/2 pathways [33]. Besides, LPS can also accelerate osteoclast differentiation by activating NF-κB-NFATc1 signal pathway [34]. In this study, we found that LPS can increase the expressions of TRAPpositive cells, osteoclasts-related genes and pro-in ammatory cytokines in RAW264.7 cells.…”
Section: Discussionsupporting
confidence: 57%
“…Studies have demonstrated that LPS can promote osteoclast differentiation by enhancing COX-2 expression and activating RANK, JNK and ERK1/2 pathways [33]. Besides, LPS can also accelerate osteoclast differentiation by activating NF-κB-NFATc1 signal pathway [34]. In this study, we found that LPS can increase the expressions of TRAPpositive cells, osteoclasts-related genes and pro-in ammatory cytokines in RAW264.7 cells.…”
Section: Discussionsupporting
confidence: 57%
“…STAT3 signaling pathway was regulated by the activation of PI3K-Akt in cell proliferation and cell differentiation [12]. A recent study reported that LPS induced osteoclastogenesis via the activation of NF-κB-NFATc1 and STAT3 signaling pathways, which were significantly blocked by treatment with diallyl disulfide [13].…”
Section: Introductionmentioning
confidence: 98%
“…The results showed that curcumin markedly attenuated the formation Because bone resorption capacity directly reflects the function of osteoclasts, hydroxyapatite-coated 24-well plates were used in this study. 22,23 After incubation in osteoclast induction medium for 4 days, the medium was replaced with medium containing 0, 1.25, 5 or 20 μmol/L curcumin, and the cells were cultured for an additional 2 days. The area of bone resorption significantly increased without curcumin intervention in the control group; however, the formation of osteoclastic resorption pits decreased as the curcumin concentration increased (Figure 2B,D).…”
Section: Curcumin Interfered With the Function Of Osteoclastsmentioning
confidence: 99%
“…Scale bar = 100 μm of F-actin rings as the curcumin concentration increased, whereas numerous well-organized F-actin rings were observed without curcumin treatment(Figure 2A,C).Because bone resorption capacity directly reflects the function of osteoclasts, hydroxyapatite-coated 24-well plates were used in this study 22,23. A, Chemical structure of curcumin (MW = 368.37).…”
mentioning
confidence: 99%